Soil carbon sequestration in a changing global environment - Macías, Felipe; Camps Arbestain, Marta (Mitigation and adaptation strategies for global change, 2010)
Throughout its long history the Earth has undergone warm periods with high atmospheric concentrations of greenhouse gases (GHG), and has responded with different buffering mechanisms whereby atmospheric C has been transferred to other geochemical compartments. Strategies for the mitigation and adaptation to the current climatic forcing may thus be generated by the acceleration of such natural mechanisms, especially those involved in short cycles, mainly in the biosphere and the pedosphere. Although these contain smaller C stocks than other compartments (< 0.01% of the total C), they circulate large amounts of C from the atmosphere through photosynthesis and mineral weathering (e.g., 120 Pg C are circulated through terrestrial ecosystems and total C in the atmospheric compartment is 805 Pg C). Increased C sequestration can thus be achieved in terrestrial ecosystems, by: (1) favouring growth of biomass; (2) promoting and facilitating carbonation processes; (3) reducing erosion and favouring pedogenesis; (4) developing organic matter-rich horizons; (5) recovering degraded or contaminated soils, and/or (6) managing waste by use of systems that minimize emissions of GHG. Within the latter option, the following actions are considered here in more detail: 1) production of Technosols, and 2) production of biochar. All of the above options should form part of a strategy for the mitigation and adaptation to global climate change. In this review, we analyze those focused on promoting soil conservation, soil restoration and soil formation.